2010
DOI: 10.1086/650997
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CD8 T Cells Predicts Progression of HIV Infection in Women Coinfected with Hepatitis C Virus

Abstract: Background Because activation of T cells is associated with human immunodeficiency virus (HIV) pathogenesis, CD4 and CD8 activation levels in patients coinfected with HIV and hepatitis C virus (HCV) may explain conflicting reports regarding effects of HCV on HIV disease progression. Methods Kaplan-Meier and multivariate Cox regression models were used to study the risk of incident clinical AIDS and AIDS-related deaths among 813 HCV-negative women with HIV infection, 87 HCV-positive nonviremic women with HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 50 publications
5
66
1
3
Order By: Relevance
“…It even correlates with CD4 1 T cell counts better than HIV RNA levels and could be used as an effective clinical prognostic indicator. 6 However, the molecular contributors to this immune activation in HIV/SIV infection remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It even correlates with CD4 1 T cell counts better than HIV RNA levels and could be used as an effective clinical prognostic indicator. 6 However, the molecular contributors to this immune activation in HIV/SIV infection remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, it has been accepted that in addition to the direct infection of CD4 1 T lymphocytes by HIV virions, chronic immune activation in HIV-infected human and simian immunodeficiency virus (SIV)-infected non-natural hosts, such as rhesus macaques and cynomolgus macaques, may greatly contribute to the pathogenesis of AIDS. [2][3][4][5][6][7] Accumulated evidence suggests that large amounts of type I interferons (IFNs) produced by activated plasmacytoid dendritic cells (pDCs) might play a critical role in this chronic immune activation during HIV-1 infection. Clinical strategies aimed at inhibiting pDC activation could effectively counter disease progression in HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…coinfections [20], damage to gut integrity, leakage of gut microbial products [21], damage to the lymphoid tissues, and loss of T regulatory (Treg) cells [22][23][24]. Several studies have shown a clear relationship between markers of immune activation and viral replication; however, it is currently unclear whether immune activation during ART drives viral persistence or whether viral persistence drives immune activation or both, as reviewed in [25].…”
Section: Key Pointsmentioning
confidence: 99%
“…A meta-analysis of eight trials showed that the mean increase in the CD4 cell count in coinfected patients was 33 cells/mm 3 less than that for HIV-infected patients without HCV infection [72], and these results have been confirmed in a more recent meta-analysis in which also an increase in AIDS events was seen in coinfected patients [73]. A chronic HCV coinfection contributes to systemic inflammation and immune activation in coinfected individuals which may in return lead to progression of their HIV disease [74]. HCV may therefore contribute to 'accelerated aging' which now has increasingly been described in HIV-infected individuals [75].…”
Section: The Impact Of Hepatitis C Virus On Hivmentioning
confidence: 78%